Impacts of urease inhibitors on nitrogen assimilation in wheat and on reducing nitrogen losses - Drame, Marieme (Cranfield University, 2024)
A major global challenge for the 21st century is to ensure food security and sustainable development while limiting the adverse impact of agricultural reactive nitrogen (Nr) pollution and global warming greenhouse gas emissions (GHG). Climate change mitigation and adaptation strategies, with varying effectiveness, have been implemented across different regions in this perspective. The use of enhanced efficiency N fertilisers (EEF) in agriculture is a potential management strategy towards this aim, with documented benefits but with existing knowledge gaps. In this thesis, the efficacy of EEF, particularly urease inhibitors (UI), was determined under warmer, dryer climatic conditions as are expected to occur more frequently under climate change scenarios. Additionally, the potential of UI to improve nitrogen use efficiency (NUE) and enhance the tolerance of wheat varieties to drought stress at different N rates was evaluated, as well as the influence of UI on plant N assimilation and potential contribution to nitrous oxide (N₂O) emissions. The effects of high soil temperature (>25℃) and low soil moisture (<40% water filled pore space; WFPS) on emissions of ammonia (NH₃ ) and N₂O following application of urea to soil was assessed, and the efficacy of UI in reducing N losses. The findings suggest that treatment of urea with UI effectively reduces NH₃ losses at temperatures reaching 35℃, although overall effectiveness decreases with increasing temperature and low soil moisture conditions. Nitrous oxide emission was not influenced by the presence of UI but was high at soil moistures <60% WFPS. Nitrous oxide emission was also measured from wheat plants grown in soil and in a hydroponic system under low (7 kg ha⁻¹) and high N (70 kg ha⁻¹) conditions. Plants emitted more N₂O under low N growth conditions when supplied with additional potassium nitrate compared with those supplied with urea treated with UI. However, insufficient evidence was obtained from the hydroponic experiment to confirm plant N₂O formation through nitrate assimilation pathways, other than its overall contribution to N₂O emissions. Furthermore, when applied to plants under drought stressed conditions, UI did not enhance wheat tolerance to drought or increase yield and NUE. Nitrogen assimilation was influence by UI, particularly leaf urea concentration which increased in the presence of UI. Similarly, application of urea included with UI at a high N rate (180 kg ha⁻¹) resulted in lower wheat biomass and yield. Varietal differences were also observed in plant N₂O emission, drought tolerance and NUE. Overall, the findings support the use of UI as a Nr mitigation strategy under warm and dry conditions; however, for increased NUE and yield, appropriate fertiliser and crop management, specific to local conditions may be needed.
Keywords: Nitrogen fertiliser; Nitrogen metabolism; Urease inhibitor; Greenhouse gas emission; Ammonia emission; Nitrous oxide emission; Nitrogen use efficiency